The effect of elephant utilisation on the Sterculia rogersii and Adsonia digitata populations of the Kruger National Park - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.